Identification of Urban Park Quality in Taman Indonesia Kaya, Semarang - Intan Muning Harjanti (Journal of Architectural Design and Urbanism, 2020)
Based on observations and the results of the analysis, it was shown that Taman Indonesia Kaya already fulfilled the quality park standards. In the aspect of needs, the comfort factor has been fulfilled by the presence of park benches and garden lights in good condition, the cleanliness factor has been fulfilled by the existence of a trash with a sorting system, public toilets and disabled toilets in a clean condition, health factors have been fulfilled with the presence of acid trees, pandanus leaves and canna flowers, and safety factors have been fulfilled with the availability of a monitor bench gazebo and lighting lamps that function optimally. In the aspect of rights, the accessibility factor has been fulfilled, because of its strategic location and is in the city centre and traversed by the Trans Semarang route, the freedom of activity factor have been fulfilled by the existence of a fountain garden, cultural stage and green space, and the diversity of activity factors have been fulfilled by the existence of the Pandawa park , mural gates, fountain shows, cultural arts performances, and various paintings. In the meanings aspect, the place clarity factor is indicated by the presence of information boards and signage that are scattered in the corner of the park, and the sociability factor have been fulfilled by the many of spaces in the park area that can be used for socializing, such as: paving fields, sidewalks, green spaces , and the cultural stage.